Color Change of the Snapper (Pagrus auratus) and Gurnard (Chelidonichthys kumu) Skin and Eyes during Storage: Effect of Light Polarization and Contact with Ice. Issue 12 (10th November 2014) - Balaban, Murat O.; Stewart, Kelsie; Fletcher, Graham C.; Alçiçek, Zayde
Abstract Ten gurnard and 10 snapper were stored on ice. One side always contacted the ice; the other side was always exposed to air. At different intervals for up to 12 d, the fish were placed in a light box, and the images of both sides were taken using polarized and nonpolarized illumination. Image analysis resulted in average L*, a*, and b* values of skin, and average L* values of the eyes. The skin L* value of gurnard changed significantly over time while that of snapper was substantially constant. The a* and b* values of both fish decreased over time. The L* values of eyes were significantly lower for polarized images, and significantly lower for the side of fish exposed to air only. This may be a concern in quality evaluation methods such as QIM. The difference of colors between the polarized and nonpolarized images was calculated to quantify the reflection off the surface of fish. For accurate measurement of surface color and eye color, use of polarized light is recommended.